2009
DOI: 10.1088/0960-1317/19/7/074015
|View full text |Cite
|
Sign up to set email alerts
|

Selective nucleation in silicon moulds for diamond MEMS fabrication

Abstract: We present a new and original approach for the fabrication of diamond MEMS using MPCVD. This process does not rely on diamond etching using conventional techniques such as e.g. RIE: here our MEMS structures are geometrically defined using silicon moulds in which diamond is grown selectively. The moulds can be prepared from silicon using DRIE and enabling a wide range of geometries. The critical point is the selectivity of diamond growth which dramatically depends on the nucleation process. Two nucleation metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 13 publications
(16 reference statements)
0
25
0
Order By: Relevance
“…Consequently, the growth of porous diamond structures was observed in those areas. Previously it was shown that metal mask allowed a prolonged plasma etching time up to 20 min, see the work of Bongrain et al [2]. In such case, the residual density of parasitic crystal decreased down to 5 Â 10 5 cm À2 .…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…Consequently, the growth of porous diamond structures was observed in those areas. Previously it was shown that metal mask allowed a prolonged plasma etching time up to 20 min, see the work of Bongrain et al [2]. In such case, the residual density of parasitic crystal decreased down to 5 Â 10 5 cm À2 .…”
mentioning
confidence: 94%
“…Adequately, developing of a suitable structuring technique is needed for realization of any device [1,2]. However, diamond chemical inertness and mechanical hardness make conventional structuring methods less favorable.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Various pre-or post growth techniques have been developed to fabricate surfaces of wished features. Only briefly, these techniques include reactive ion etching [7,8] involving EBL [9], ink-jet printing of diamond seeds [10], selective area deposition [11,12] including selective etching of substrate [13]. However, only a limited number of above mentioned techniques allows the fabrication of geometrically ordered arrays or templates.…”
Section: Introductionmentioning
confidence: 99%